THE INTERPLAY OF SIGN AND SIMULTANEOUS INTERPRETING (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article explores the intricate relationship between sign and simultaneous interpreting, examining how the principles and practices of sign language interpretation intersect with the demanding modality of simultaneous interpretation. While traditionally viewed as distinct fields, a deeper analysis reveals significant overlaps in cognitive demands, strategic approaches, and the ultimate goal of facilitating effective cross-linguistic communication. This article delves into the theoretical underpinnings of both disciplines, analyzes the unique challenges and adaptations required for simultaneous sign language interpreting, discusses current research and technological advancements, and proposes future directions for the field. By integrating insights from both auditory and visual interpreting, this research aims to foster a more comprehensive understanding of the interpreter’s role in bridging linguistic and cultural divides.